2012
DOI: 10.1016/j.jri.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the transcriptional response of human decidual cells to lipopolysaccharide stimulation

Abstract: Decidual cells are central to innate immunity at the maternal/fetal interface. We sought to characterize the response of decidual cells to stimulation and then removal of lipopolysaccharide (LPS) using a whole genome approach. Decidual cells were isolated from term unlabored cesarean sections. Cells were stimulated with LPS and RNA isolated both prestimulation and 2 and 24 h post-stimulation. Media were changed and RNA extracted 48 h later. Gene expression was measured using Agilent 44K whole genome microarray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…[58][59][60][61] The dTHESC cells did not demonstrate significantly increased production of CCL5, IL-10, TGFβ 1, MIC-1, G-CSF, or IL-1β following LPS exposure. Prior studies have reported mixed results in TNFα production in response to LPS by decidual stromal cells, 58,62,63 and VEGF was below the limit of detection in our system. In our studies, PMA-differentiated THP-1 macrophage-like cells produced significant increases in TNFα in response to LPS.…”
Section: Discussioncontrasting
confidence: 57%
“…[58][59][60][61] The dTHESC cells did not demonstrate significantly increased production of CCL5, IL-10, TGFβ 1, MIC-1, G-CSF, or IL-1β following LPS exposure. Prior studies have reported mixed results in TNFα production in response to LPS by decidual stromal cells, 58,62,63 and VEGF was below the limit of detection in our system. In our studies, PMA-differentiated THP-1 macrophage-like cells produced significant increases in TNFα in response to LPS.…”
Section: Discussioncontrasting
confidence: 57%
“…With regards to additional transcriptional effects, studies using primary human DSCs have illustrated that LPS increases the expression of a number of genes in the NF-κB pathway, including monocyte chemoattractant protein-1 (MCP-1) [31], IL-1β [31, 32], colony stimulating factor-2 (CSF-2) [31] and IL-8 [16, 31]. Other studies utilizing primary human DSCs observed increased gene expression of TNF-α [32, 33], IL-6 [17, 32, 33], lipid metabolism genes ( e.g. , those involved in prostaglandin production) [32], and decreased solute carrier family 40 member 1 (SLC40A1), which is key in modulating iron levels [32].…”
Section: Methodsmentioning
confidence: 99%
“…Other studies utilizing primary human DSCs observed increased gene expression of TNF-α [32, 33], IL-6 [17, 32, 33], lipid metabolism genes ( e.g. , those involved in prostaglandin production) [32], and decreased solute carrier family 40 member 1 (SLC40A1), which is key in modulating iron levels [32]. Utilizing an immortalized line of human decidualized endometrial stromal cells, Grasso and colleagues assessed responses to LPS, which also elicited increased gene expression of regulated on activation, normal T cell expressed and secreted (RANTES), MCP-1 and IL-8 [34].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into human decidual cells has demonstrated that LPS influences the expression of genes engaged in lipid metabolism, including cholesterol and steroid biosynthesis [62]. Proprotein convertase subtilisin/kexin type 9 (product of PCSK9), the key regulator of serum cholesterol levels, inhibits LPS removal from the bloodstream [63].…”
Section: Discussionmentioning
confidence: 99%